Intensifying Continuous Production of Gag-HA VLPs at High Cell Density Using Stable Insect Cells Adapted to Low Culture Temperature - Fernandes, Bárbara; Correia, Ricardo; Alves, Paula M.; Roldão, António (Frontiers in Bioengineering and Biotechnology, 2022)
Protein production processes based on stable insect cell lines require intensification to be competitive with the insect cell-baculovirus expression vector system (IC-BEVS). High cell density (HCD) cultures operate continuously, capable of maintaining specific production rates for extended periods of time which may lead to significant improvements in production yields. However, setting up such processes is challenging (e.g., selection of cell retention device and optimization of dilution rate), often demanding the manipulation of large volumes of culture medium with associated high cost. In this study, we developed a process for continuous production of Gag virus–like particles (VLP) pseudotyped with a model membrane protein (influenza hemagglutinin, HA) at HCD using stable insect cells adapted to low culture temperature. The impact of the cell retention device (ATF vs. TFF) and cell-specific perfusion rate (CSPR) on cell growth and protein expression kinetics was evaluated. Continuous production of Gag-HA VLPs was possible using both retention devices and CSPR of 0.04 nL/cell.d; TFF induces higher cell lysis when compared to ATF at later stages of the process (kD = 0.009 vs. 0.005 h−1, for TFF and ATF, respectively). Reducing CSPR to 0.01–0.02 nL/cell.d using ATF had a negligible impact on specific production rates (rHA = 72–68 titer/109 cell.h and rp24 = 12–11 pg/106 cell.h in all CSPR) and on particle morphology (round-shaped structures displaying HA spikes on their surface) and size distribution profile (peaks at approximately 100 nm). Notably, at these CSPRs, the amount of p24 or HA formed per volume of culture medium consumed per unit of process time increases by up to 3-fold when compared to batch and perfusion operation modes. Overall, this work demonstrates the potential of manipulating CSPRs to intensify the continuous production of Gag-HA VLPs at HCD using stable insect cells to make them an attractive alternative platform to IC-BEVS.